MEDULA ÓSSEA: POR QUE, ONDE E COMO COLHER DE CÃES E GATOS? - Rodrigues, Cláudia M.; Cruz, Pamela d. L. T. d.; Basso, Paula C.; Fritzen, Henrique S.; Müller, Daniel C. d. M. (Salão do Conhecimento, 2013)
Resumo